Keragaan beberapa Varietas Sorgum terhadap Aplikasi Kitosan Iradiasi - Ferdifta Wahyu Anggita; Puji Harsono; Retno Wijayanti; Supriyono Supriyono (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Sorghum is a versatile, drought-resistant cereal crop. Increasing sorghum production needs special attention, although Indonesia has the potential for sorghum development. Irradiated chitosan can be used as a plant growth promoter and organic fertilizer to improve the performance of sorghum. This study aims to provide recommendations for sorghum varieties that are suitable for development and planting in dry land and are known to be able to control pests organically with the application of chitosan irradiation with optimum concentration. The experimental design was a separate plot with sorghum varieties (Numbu, Keller, and Kawali) as the main plot and the irradiated concentrations of chitosan (without irradiation, 2, 4, and 6 ml.L-1) as subplots. The results showed that the sorghum variety and the optimum chitosan irradiation concentration of 2.76 and 5.15 ml.L-1 increased the dry weight of stover per plant by 93.04 g per plant and increased the sugar content of sorghum with Brix 15.03%. The varieties of Numbu, Keller, and Kawali significantly affected plant height, number of leaves, weight of 100 seeds, and plant fresh weight per plot or forage of sorghum.